Current And Future Trends In The Teaching Of Direct Posterior Resin Composites In Malaysian Dental Schools: A Cross-sectional Study - Preena Sidhu; Omer Sheriff Sultan; Swarna Yerebairapura Math; Normaliza Binti Ab Malik; Nairn H.F. Wilson; Christopher D. Lynch; Igor R. Blum; Umer Daood (Elsevier Ltd., 2024)
Indexed by WOS/SCOPUS/ERA